Enzyme activities in parotid saliva of patients with the restrictive type of anorexia nervosa. (April 2017) - Paszynska, Elzbieta; Slopien, Agnieszka; Dmitrzak-Weglarz, Monika; Hannig, Christian
Highlights: In patients with anorexia nervosa (AN) there are conflicting reports concerning changes in salivary composition. Investigation of resting parotid secretion and enzyme activities: amylase, aspartate amino transferase (AST), lysozyme, peroxidase, serine and acidic proteases are proposed. The reduced flow rate and enzyme activities levels suggest that AN does not only affect the quantity of the saliva but also its quality and, its biological functions. Abstract: Objective: In patients with anorexia nervosa (AN) specific signs may occur in the oral cavity, but there are conflicting reports about their significance, especially concerning changes in salivary composition. The aim of this clinical study was to evaluate the resting parotid flow rate (PFR) and the activity of the following enzymes in parotid saliva: amylase, aspartate amino transferase (AST), lysozyme, peroxidase, serine and acidic proteases in the acute phase of the restrictive type of AN and to compare the findings with those in healthy controls. Design: Forty-one subjects participated (20 patients with AN, 21 matched healthy controls), parotid saliva was collected using a modified Lashley cap at rest. Enzyme activities were measured with fluorimetric and photometric assays. Results: The unstimulated PFR was significantly lower than in the controls, lysozyme and AST activity was significantly lower, and amylase showed a high inter-individual variability. A positive correlation for amylase and lysozyme and negative ones for lysozyme and BMI, lysozyme and IBW%, serine protease and salivary flow were observed. Conclusions: The reduced PFR and enzyme activities levels suggest that AN does not only affect the quantity of the saliva but also its quality and, its biological functions. The results obtained should help to provide a better understanding of the effect of AN disease on the pathogenesis of at least some oral diseases. Further research is needed on any possible role of reduced lysozyme and transaminase activity in maintaining oral protection against external toxic agents and bacteria.